2017
DOI: 10.1111/hel.12409
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Helicobacter pylori

Abstract: As Helicobacter pylori infects half the world's population and displays an extensive intraspecies diversity, genomics is a powerful tool to understand evolution and disease, to identify factors that confer higher risk of severe sequelae, and to find new approaches for therapy both among bacterial and host targets. In line with these objectives, this review article summarizes the major findings in Helicobacter genomics in papers published between April 2016 and March 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Two well‐defined clinical entities provide a vivid illustration of disrupted microbiome‐host interactions: Clostridioides difficile‐ associated disease (CDAD) and Helicobacter pylori infection. The former serves as a dramatic reminder of the consequences of iatrogenic disruptions of a microbiome that, when intact, serves to protect us against pathogens (Britton & Young, ; Schäffler & Breitrück, ), and the latter exemplifies how host genome, bacterial properties and the immune response conspire to produce various disease phenotypes (Noto & Peek, ; Thorell, Lehours, & Vale, ; Waskito, Salama, & Yamaoka, ).…”
Section: What Do We Know?mentioning
confidence: 99%
“…Two well‐defined clinical entities provide a vivid illustration of disrupted microbiome‐host interactions: Clostridioides difficile‐ associated disease (CDAD) and Helicobacter pylori infection. The former serves as a dramatic reminder of the consequences of iatrogenic disruptions of a microbiome that, when intact, serves to protect us against pathogens (Britton & Young, ; Schäffler & Breitrück, ), and the latter exemplifies how host genome, bacterial properties and the immune response conspire to produce various disease phenotypes (Noto & Peek, ; Thorell, Lehours, & Vale, ; Waskito, Salama, & Yamaoka, ).…”
Section: What Do We Know?mentioning
confidence: 99%
“…In fact there is evidence of high adaptability to the new environment, with new subpopulations of H. pylori constantly emerging in different regions of the world. Recent studies highlighted that in the span of 500 years of migration to the Latin America, already there have been sequenced distinct genomes specific to these populations [11]. This diversity is also present when analyzing severity of the infection across the world, and manifests itself is in virulence factors.…”
Section: State Of the Knowledgementioning
confidence: 99%
“…These studies have shown that H . pylori display extensive intraspecies diversity 18 and that this diversity appears to be influenced by the presence of mobile genomic elements, including prophages 9 …”
Section: Introductionmentioning
confidence: 99%